Jawabanmu

2014-04-20T21:51:09+07:00
cos²b  + (1+sin b)(1+sin b)          = 2 sec b
      (1+ sin b) (cos b)
cos²b + 1 + sin b + sin b + sin²b  = 2 sec b
       (1+ sin b) (cos b)
1 - sin²b +1 + 2 sin b + sin²b       = 2 sec b
           (1+ sin b) (cos b)
       2 + 2 sin b                          = 2 sec b
   (1+ sin b) (cos b)
       2(1+ sin b)                          = 2 sec b
    (1+ sin b) (cos b)
         2 (1)                                 = 2 sec b
       (cos b)
           2 sec b                           = 2 sec b (terbukti)    
1 1 1